2016
DOI: 10.14348/molcells.2016.0210
|View full text |Cite
|
Sign up to set email alerts
|

Highly Expressed Integrin-α8 Induces Epithelial to Mesenchymal Transition-Like Features in Multiple Myeloma with Early Relapse

Abstract: Despite recent groundbreaking advances in multiple myeloma (MM) treatment, most MM patients ultimately experience relapse, and the relapse biology is not entirely understood. To define altered gene expression in MM relapse, gene expression profiles were examined and compared among 16 MM patients grouped by 12 months progression-free survival (PFS) after autologous stem cell transplantation. To maximize the difference between prognostic groups, patients at each end of the PFS spectrum (the four with the shortes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Meanwhile, the phosphorylation of ERK1/2 was augmented compared to the control cells. A number of studies reported that integrins promote cancer metastasis through epithelial-mesenchymal transition (EMT) [48,49], which are in line with our findings. The IHC data revealed no difference in the expression of ITGA2 in primary and tumor tissues with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the phosphorylation of ERK1/2 was augmented compared to the control cells. A number of studies reported that integrins promote cancer metastasis through epithelial-mesenchymal transition (EMT) [48,49], which are in line with our findings. The IHC data revealed no difference in the expression of ITGA2 in primary and tumor tissues with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with effects in the deregulation of integrins. It is known, in fact, that their up or downregulation [ 35 , 36 ] is responsible to modulate cell invasion and migration in cancer microenvironment. We finally confirmed the inhibitory activity of CPTH2 on the cell invasiveness properties, performing an in vitro wound healing scratch tests.…”
Section: Resultsmentioning
confidence: 99%
“…The gene ITGA8 , among other studies, was studied in multiple myeloma cell lines since it was discovered its high expression in patients with early relapse [ 125 ]. The ITGA8 overexpression in this cell model was associated with an induction of stemness features and epithelial-mesenchymal transition-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%